Invasive Predators in New Zealand - King, Carolyn M. author. aut Link
XXXIV, 343 p. 40 illus., 30 illus. in color.
Keywords: The story of invasive species in New Zealand is unlike any other in the world. By the mid-thirteenth century, the main islands of the country were the last large landmasses on Earth to remain uninhabited by humans, or any other land mammals. New Zealand’s endemic fauna evolved in isolation until first Polynesians, and then Europeans, arrived with a host of companion animals such as rats and cats in tow. Well-equipped with teeth and claws, these small furry mammals, along with the later arrival of stoats and ferrets, have devastated the fragile populations of unique birds, lizards and insects. Carolyn M. King brings together the necessary historical analysis and recent ecological research to understand this long, slow tragedy. As a comprehensive historical perspective on the fate of an iconic endemic fauna, this book offers much-needed insight into one of New Zealand’s longest-running national crises. .